(untitled) (Journal of Environmental Science and Natural Resources, 2021)
Bangladesh has been facing rapid and unplanned urbanization for last several years resulting devastating change to vegetation, fresh water body and bare soil in this area. This integrated study aimed to find out the trend of urbanization and land cover changes in Chuandanga, a western district of Bangladesh. This downscaled approach used GIS and remote sensing techniques for supervised land cover classification of Landsat images for last five years (2014-2018). The study has portrayed an increasing trend in built up area and bare soil whereas a decreasing trend in vegetation and water body. Meanwhile, it has been found that change in built up area and vegetation cover is strongly correlated whilst built area is increased by 1.28% (14.84 sq.km) and vegetation decreased by 16.54% (191.96 sq.km) during this period. Moreover, it is also observed that rapid growth of urban areas has a considerable influence on decreasing water body and bare soil as well as the changing pattern showing the forthcoming urbanization in this city. This study shows the importance of urban expansion for achieving Sustainable Development Goals (SDG) in particular Goal 11, Sustainable Cities. Environ. Sci. & Natural Resources, 12(1&2): 37-42, 2019